Determinants of Profitability in Digital Banking: The Moderating Role of CKPN - Hendrik Ali; Septiana Sihombing (Jurnal Manajemen dan Perbankan (JUMPA), 2025)
This research seeks to evaluate the determinants of the ROA ratio in connection to the financial ratios CAR, NPL, and LDR, while also investigating the moderating impact of CKPN on this connection. The researcher used secondary information from the financial statements of six digital banks listed on the BEI (Stock Exchange Indonesia) for the period spanning 2020 to 2024, utilizing SPSS version 27. The study findings indicated that CAR positively influences ROA; nevertheless, this effect lacks significance. Conversely, NPL has a beneficial influence on ROA, which opposes the prevailing idea that NPL should diminish profitability. The LDR ratio influences ROA; however, its effect is minimal. CKPN, in its capacity as a moderator, may just enhance the impact of CAR on ROA but is unable to modify the link between NPL and LDR with ROA. This study's originality is attributed to the incorporation of CKPN as a moderating variable within the framework of digital banking in Indonesia, with the finding that NPL positively influences ROA. This research highlights the need for flexible strategies in the management of CKPN to foster stability and innovation in digital finance. Abstrak - Penelitian ini bermaksud untuk menganalisis determinan rasio ROA dari dampak rasio keuangan CAR, NPL, dan LDR serta menguji peran CKPN sebagai variabel moderasi dalam memperkuat hubungan tersebut. Peneliti mengadopsi data sekunder dari laporan tahunan keuangan enam bank digital yang terdaftar di Bursa Efek Indonesia dari jangka waktu 2020 sampai 2024. Data dianalisis memanfaatkan regresi linier berganda melalui program SPSS versi 27. Temuan ini mengungkapkan rasio CAR berdampak positif kepada ROA, namun pengaruh tersebut tidak signifikan. Sedangkan NPL berdampak positif terhadap ROA, yang bertentangan dengan teori umum bahwa NPL seharusnya menurunkan profitabilitas. Rasio LDR kemungkinan dampak terhadap ROA, namun tidak relevan. CKPN menjadi variabel moderasi hanya mampu menegakkan pengaruh CAR terhadap ROA, namun tidak dapat memoderasi hubungan NPL dan LDR kepada ROA. Kebaruan dari penelitian ini terletak pada penggunaan CKPN sebagai variabel moderasi dalam konteks bank digital di Indonesia, serta temuan bahwa NPL memiliki dampak positif kepada ROA. Implikasi penelitian ini adalah perlunya kebijakan adaptif dalam pengelolaan CKPN untuk mendukung stabilitas dan inovasi keuangan digital.